Highly efficient photoelectrocatalytic degradation for ciprofloxacin with a new polyoxometalate-based metal–organic hybrid/BiVO4 photoanode - Yuting Song; Tao Bo; Ji-Cheng Ma; Jian-Fang Ma (Green Energy & Environment)
Efficient removal of antibiotics is of great significance for the sustainability of aquatic ecosystems. In this work, a new polyoxometalate-based metal–organic hybrid material [Ag3L0.5(HSiW12O40)]·2C2H5OH·2CH3CN (Ag-L-SiW12) was prepared by using Keggin-type polyoxometalate anion and thiacalix[4]arene-based ligand (L) via solvothermal method. Subsequently, a composite heterojunction Ag-L-SiW12@BiVO4 photoanode was fabricated by loading Ag-L-SiW12 on the surface of BiVO4. The photoelectrocatalytic degradation performance of ciprofloxacin (CIP) was explored under the simulated solar radiation. Remarkably, the CIP degradation efficiency reached 93% within 240 min using the optimal Ag-L-SiW12@BiVO4 photoanode, which is approximately 2 and 23 times those of pristine BiVO4 and Ag-L-SiW12, respectively. Furthermore, density functional theory (DFT) calculations were conducted to elucidate the role of Ag-L-SiW12 during the photoelectrocatalytic process. This work offers an example of the efficient composite photoelectrocatalysts for the treatment of antibiotic wastewater.